HD 3298: Biofortified, climate-resilient, high-yielding wheat variety for very late sown conditions of North-Western Plains of India - Yadav, Rajbir; Gaikwad, Kiran Bapusaheb; Kumar, Manjeet; Singh, Gyanendra Pratap; Sharma, Ram Kumar; Singh, Pradeep Kumar; Kumar, Naresh; Hanumanthappa, Prashantha Babu; Mahendru Singh, Anju; Sivasamy, Murugasamy; Nallathambi, Peru; Singh, Vaibhav Kumar; et al. (Journal of Cereal Research, 2022)
HD 3298 is a biofortified wheat variety having high iron (43.1 ppm) and protein (12.12 %) content with tolerance to terminal heat stress. This variety has a higher yield potential of 47.4 q ha-1 under very late sown conditions. It possesses a high level of resistance against stripe rust, leaf rust, and other important diseases. It has better agronomic attributes and has better adaption to sowing time from timely to very late. This variety has a perfect Glu score (10) with excellent grain quality parameters.